Research on the Enhancement of Ideological and Political Education in Courses at Universities and Colleges Under a New Situation - Yanyan Liu (Journal of Advanced Research in Education, 2025)
Amid the changes in economic situations, higher requirements have been set up for the cultivation of economic talent. Professional education should be organically integrated with ideological and political education, and only firm political directions, and correct directions of education can help achieve the goal of comprehensive talent cultivation. In particular, in the context of the normalization of the epidemic, strengthening the psychological guidance for students by enhancing the ideological and political education in courses is an important path of moral education for online and offline teaching and students under lockdown. This study takes economics as an example and discusses the objective need for universities and colleges to enhance ideological and political education, the objectives of the enhancement, and the ways to realize it.